1991
DOI: 10.1017/s0043174500071435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wild Oat (Avena fatua) Infestations on Light Interception and Growth Rate of Wheat (Triticum aestivum)

Abstract: Wild oat reduced light penetration and growth of dwarf hard red spring wheat in field experiments performed under nonlimiting nitrogen and moisture conditions. Wild oat grew taller than wheat and had a greater portion of its canopy above 60 cm at maturity. Light penetration in a mixed canopy was similar to that in a monoculture wheat canopy when wild oat was clipped to the height of the wheat. A mathematical model was developed which accurately predicted the reduction in the growth rate of wheat from wild oat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 11 publications
0
47
1
1
Order By: Relevance
“…These sensitivity analyses are supported by experimental work. Several studies have demonstrated that shorter wheat varieties, and particularly dwarf wheats, suffer greater yield losses due to competition from wild oat species than taller varieties (Balyan et al, 1991;Cudney et al, 1991). Thurston (1962) noted that winter cereals strongly suppress the growth of springemerging A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sensitivity analyses are supported by experimental work. Several studies have demonstrated that shorter wheat varieties, and particularly dwarf wheats, suffer greater yield losses due to competition from wild oat species than taller varieties (Balyan et al, 1991;Cudney et al, 1991). Thurston (1962) noted that winter cereals strongly suppress the growth of springemerging A .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of A . fatua to reduce crop yields has been attributed to its height and leaf area distribution which reduce light penetration to the crop canopy (Cudney, Jordan & Hall, 1991;Morishita, Thill & Hammel, 1991;Rooney, 1991), its high net assimilation rate during the early growth stages (Thurston, 1959), and to the role of its extensive root system in depriving the crop of water and nutrients when these resources are limiting (Pavlychenko & Harrington, 1935;Carlson & Hill, 1986). The impact of A .…”
Section: Introductionmentioning
confidence: 99%
“…Taller varieties are likely to be more competitive than shorter ones as competition for light increases (Cudney et al 1991). The relative importance of plant height decreases if compensated for by other traits.…”
Section: Phosphorusmentioning
confidence: 99%
“…Semidwarf cultivars can produce high grain yield in conventional management, but they often produce significantly lower yield in organic management due to weaker weed competitiveness. Taller plants exhibit better competitive ability against weeds than shorter ones, mainly due to better light interception that directly alters the photosynthetic activity of crop plants (Cudney et al, 1991;Mason et al, 2007aMason et al, , 2007b. Wheat breeders may therefore need to consider developing taller cultivars than semidwarfs for organic agriculture, without significantly affecting plant maturity, lodging resistance, and other qualitative traits.…”
mentioning
confidence: 99%